Brill's companion to military defeat in ancient Mediterranean society - Clark, Jessica Homan, 1980-; Turner, Brian (Historian) (Brill's Companions to Classical Studies, 2018)
In Brill's Companion to Military Defeat in Ancient Mediterranean Society , Jessica H. Clark and Brian Turner lead a re-examination of how Near Eastern, Greek, and Roman societies addressed - or failed to address - their military defeats and casualties of war. Original case studies illuminate not only how political and military leaders managed the political and strategic consequences of military defeats, but also the challenges facing defeated soldiers, citizens, and other classes, who were left to negotiate the meaning of defeat for themselves and their societies. By focusing on the connections between war and society, history and memory, the chapters collected in this volume contribute to our understanding of the ubiquity and significance of war losses in the ancient world.